A BK (Slo1) channel journey from molecule to physiology - Contreras, Gustavo F (Landes Bioscience, 2013)
Calcium and voltage-activated potassium (BK) channels are key actors in cell physiology, both in neuronal and non-neuronal cells and tissues. Through negative feedback between intracellular Ca(2+) and membrane voltage, BK channels provide a damping mechanism for excitatory signals. Molecular modulation of these channels by alternative splicing, auxiliary subunits and post-translational modifications showed that these channels are subjected to many mechanisms that add diversity to the BK channel α subunit gene. This complexity of interactions modulates BK channel gating, modifying the energetic barrier of voltage sensor domain activation and channel opening. Regions for voltage as well as Ca(2+) sensitivity have been identified, and the crystal structure generated by the 2 RCK domains contained in the C-terminal of the channel has been described. The linkage of these channels to many intracellular metabolites and pathways, as well as their modulation by extracellular natural agents, has been found to be relevant in many physiological processes. This review includes the hallmarks of BK channel biophysics and its physiological impact on specific cells and tissues, highlighting its relationship with auxiliary subunit expression.